The Arabidopsis bZIP19 and bZIP23 Activity Requires Zinc Deficiency – Insight on Regulation From Complementation Lines - Lilay, Grmay H.; Castro, Pedro Humberto; Campilho, Ana; Assunção, Ana G. L. (Frontiers in Plant Science, 2019)
All living organisms require zinc as an essential micronutrient. Maintaining appropriate intracellular zinc supply, and avoiding deficiency or toxic excess, requires a tight regulation of zinc homeostasis. In Arabidopsis, bZIP19 and bZIP23 (basic-leucine zipper) transcription factors are the central regulators of the zinc deficiency response. Their targets include members of the ZIP (Zrt/Irt-like Protein) transporter family, involved in cellular zinc uptake, which are up-regulated at zinc deficiency. However, the mechanisms by which these transcription factors are regulated by cellular zinc status are not yet known. Here, to further our insight, we took advantage of the zinc deficiency hypersensitive phenotype of the bzip19 bzip23 double mutant, and used it as background to produce complementation lines of each Arabidopsis F-bZIP transcription factor, including bZIP24. On these lines, we performed complementation and localization studies, analysed the transcript level of a subset of putative target genes, and performed elemental tissue profiling. We find evidence supporting that the zinc-dependent activity of bZIP19 and bZIP23 is modulated by zinc at protein level, in the nucleus, where cellular zinc sufficiency represses their activity and zinc deficiency is required. In addition, we show that these two transcription factors are functionally redundant to a large extent, and that differential tissue-specific expression patterns might, at least partly, explain distinct regulatory activities. Finally, we show that bZIP24 does not play a central role in the Zn deficiency response. Overall, we provide novel information that advances our understanding of the regulatory activity of bZIP19 and bZIP23.